FINITE ELEMENT SIMULATIONS FOR THE COMPREHENSION OF PHYSICAL PHENOMENA INVOLVED IN ELECTRIC IMPEDANCE TOMOGRAPHY OF MASONRY STRUCTURES - Naasson, Alcantara [UNESP]; Ramos Luis, F.; Paulo, Mendes; Joao, Ferreira; Francisco, Fernandes; Lourenco Paulo, B. (Dolnoslaskie Wydawnictwo Edukacyjne-dwe, 2012)
The paper describes the preliminary studies of University of Minho on the use of Electric Impedance/Resistance Tomography to assess masonry structures. The study is focused on the analysis of values of current and voltage resulting from the use of an electrical source with voltage and frequency values from a distribution network. The analysis is made from results obtained through computer simulations, using a three-dimensional model of the idealized masonry structures. A finite element program was used for the simulations. Three types of electrodes were used in simulations, and the analysis of the results led to significant conclusions. Later masonry specimens were built and a series of preliminary tests were carried out in the laboratory. The comparative analysis of simulated and experimental results allowed identifying the factors that have influence on the physical results.
Keywords: Non-Destructive Test; Electrical Impedance/Resistance Tomography; Masonry Structures